A dragon that prefers a quiet life at home. (22nd November 2018) - Unknown
The 70-kilogram lizards have little to fear, yet they seldom explore outside their natal valleys. The 70-kilogram lizards have little to fear, yet they seldom explore outside their natal valleys.